Promegranate Peel as Prophylactic Agent of Rheumatoid Arthritis : Study on MMP-9, IL-6, TNF- α, and Arthritic Score of Rheumatoid-arthritic Rats - Doti Wahyuningsih; Annisa Amilia; Meilano Setiawan Amiruddin; Asri Cahyaningrum; Laili Cinthianur Kurniasari (Journal of Tropical Life Science, 2020)
Rheumatoid arthritis (RA) is a joint disease, chronically cause permanent joint impairment leading to inability of daily life activities. Early diagnosis and preven-tive managements of RA are recommended to overcome the disease. The current drugs provide benefits for RA patients, unfortunately could not be used for long period and as prevention agents, due to the adverse effects.  Even though clinical and laboratory studies of pomegranate for osteoarthritis and RA had been done, the effects of the pomegranate peel on MMP-9, TNF-α, and IL-6 of RA are still unrevealed. TNF-α promotes inflammation process in RA and collaborates with osteoclasts to trigger osteoporosis. IL-6 shows negative effect on osteoblasts dif-ferentiation and MMP-9 stimulates cartilage degradation and inflammation mediat-ed by synovial fibroblast. This study measured TNF-α, IL-6, MMP-9, and arthri-tis score (AS) of RA rats treated with ethanolic extract of pomegranate peel (EPP) to evaluate its potency as a RA prevention agent. Male Lewis rats (three groups, five each), 200 g, received 80 mg, 160 mg, and 320 mg of EPP/rat respectively, in alternate day, within 60 days. On the 30th day, the rats were subcutaneously in-jected with 0,1 ml mycobacterium-complete Freund’s adjuvant (1 mg/mL) on plan-tar of the right hind paws to induce RA. Serum IL-6 and TNF-α were determined by ELISA.  Immunohistochemistry processed-synovial MMP-9 slices of ankle joints were evaluated by light microscope (400× magnification).  Arthritis score of Smit was used to determined AS. Data were analyzed by Kruskall Wallis, Mann Whitney U, and Pearson correlation test. p < 0.05 was significant. The EPP of 320 mg corrected serum TNF-α and IL-6, and synovial MMP-9 of RA rats (p < 0.05). No significant change was observed in arthritic score following the EPP treatment (p > 0.05). In conclusion, the results indicate the EPP may potential to be devel-oped as preventive agent of rheumatoid arthritis.